2008
DOI: 10.1002/app.28988
|View full text |Cite
|
Sign up to set email alerts
|

Studies on morphology, mechanical, thermal, and dynamic mechanical behavior of extrusion blended polypropylene and thermotropic liquid crystalline polymer in presence of compatibilizer

Abstract: Polypropylene was melt blended in a single screw extruder with thermo tropic Vectra B-950 liquid crystalline polymer (copolyester amide) in different proportions in presence of 2% of EAA ,ethylene-acrylic acid copolymer (based on PP) as a compatibilizer. The mechanical properties of such compatibilized blends were evaluated and compared in respect of their Young's Modulii, Ultimate tensile strength, percent elongation at break, and toughness to those of Pure PP. The Morphology was studied by using a polarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Compared to the nonnucleated blends, the incorporation of nucleating agents significantly increased the crystallization peak temperature of PP and LLDPE, the same trend was reported in the literature, and it was due to the nucleation effects of the nucleating agent 16. As previously reported, all authors17–22 agree that in PP‐LLDPE blends a decrease in the crystallization of PP in the presence of molten PP is attributable only to a reduction in the nuclei density, which take place from immiscible melts 23. It can be observed that melting temperature T m for pure PP was 160°C and with the addition of LLDPE reached at high temperature 161.5°C at LLDPE 40 phr was increase slightly could be caused by the dissolution of defective PP molecules into the LLDPE.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Compared to the nonnucleated blends, the incorporation of nucleating agents significantly increased the crystallization peak temperature of PP and LLDPE, the same trend was reported in the literature, and it was due to the nucleation effects of the nucleating agent 16. As previously reported, all authors17–22 agree that in PP‐LLDPE blends a decrease in the crystallization of PP in the presence of molten PP is attributable only to a reduction in the nuclei density, which take place from immiscible melts 23. It can be observed that melting temperature T m for pure PP was 160°C and with the addition of LLDPE reached at high temperature 161.5°C at LLDPE 40 phr was increase slightly could be caused by the dissolution of defective PP molecules into the LLDPE.…”
Section: Resultssupporting
confidence: 81%
“…Loss modulus increase upon increase LLDPE, as already discussed before. This increase can be due to the fact that the presence of LLDPE decreases mobility of the PP chains 19–23…”
Section: Resultsmentioning
confidence: 99%
“…Thermotropic liquid crystalline polymer (TLCP) is considered as a promising option for developing high‐performance polymers because of its good thermal stability, high strength and modulus, as well as low linear viscosity [8]. Various types of TLCP have been reported to blend with polypropylene, polycarbonate, and poly(ethylene terephthalate), etc [9–11]. The so‐called in situ fibrillation is generally formed as a rigid phase in the polymeric matrix under the shear deformation, leading to the distinct increase of the mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene acrylic acid copolymer (EAA) is commonly used as packing material, powder coat, adhesive, hot melt glue . In addition, EAA was proposed as compatibilizer for some binary immiscible blends, such as, polypropylene (PP)/thermotropic liquid crystalline polymer, low density polyethylene/polyamide 6, and poly(butylene terephthalate)/ethylene vinyl acetate copolymer blends . EAA was also blended with other polymers and fillers .…”
Section: Introductionmentioning
confidence: 99%